Prevalence of obesity and screening for diabetes among secondary school students - Yu, Edmund Wei Chang; Narwani Hussin,; Marliana Abd Rahim,; Sreevali Muthuvadivelu,; Chan, Wai Seong (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Introduction There is an increasing trend of obesity in children and adolescent globally. The objectives of this study were to identify the prevalence of overweight and obesity among students from secondary schools and to determine the mean random blood sugar (RBS) for the overweight and obese students. Methods This was a cross sectional study. Two secondary schools that were scheduled for visit by the School Health Team, Taiping in July 2016 were included. A standardized data collection sheet was used to collect the data. Overweight and obesity were defined based on WHO 2007 reference for BMI-for-age criteria. Random blood glucose was checked for overweight and obese students. Results A total of 184 school students consented and participated. 128 (69.6%) were female and 90 (48.9%) were Malays. The mean weight and height were 56.21 kg and 1.61 m respectively with BMI of 21.49 kg/m2. Overall, the prevalence of obese and overweight were 12.5% and 10.9% respectively. Among the 4 BMI groups, there were no significant difference found in sex (p=0.849) and races (p=0.536). However, there was significant difference (p=0.042) in mean RBS for obese and overweight students between races. RBS readings among overweight and obese students were within normal range with mean of 5.95 (0.67) mmol/l (range between 4.60 – 7.70 mmol/l). Conclusions The overall prevalence of overweight and obesity were comparable with other studies done in Malaysia. Nevertheless, there was no prevalence of Type II diabetes mellitus among them.